Economic Implications of Moving Toward Global Convergence on Emission Intensities - Timilsina, Govinda R. (The World Bank, 2012)
One key contentious issue in climate change negotiations is the huge difference in carbon dioxide (CO2) emissions per capita between more advanced industrialized countries and other nations. This paper analyzes the costs of reducing this gap. Simulations using a global computable general equilibrium model show that the average the carbon dioxide intensity of advanced industrialized countries would remain almost twice as high as the average for other countries in 2030, even if the former group adopted a heavy uniform carbon tax of